GABAA Receptor β3 Subunit Expression Regulates Tonic Current in Developing Striatopallidal Medium Spiny Neurons - Janssen, Megan; Yasuda, Robert P.; Vicini, Stefano (Frontiers in Cellular Neuroscience, 2011)
The striatum is a key structure for movement control, but the mechanisms that dictate the output of distinct subpopulations of medium spiny projection neurons (MSNs), striatonigral projecting and dopamine D1 receptor- (D1+) or striatopallidal projecting and dopamine D2 receptor- (D2+) expressing neurons, remains poorly understood. GABA-mediated tonic inhibition largely controls neuronal excitability and action potential firing rates, and we previously suggested with pharmacological analysis that the GABAA receptor β3 subunit plays a large role in the basal tonic current seen in D2+ MSNs from young mice (Ade et al, 2008; Janssen et al, 2009). In this study, we demonstrated the essential role of the β3 GABAA receptor subunit in mediating MSN tonic currents using conditional β3 subunit knock-out (β3f/fDrd2) mice. Cre-lox genetics were used to generate conditional knock-out animals where Cre recombinase was expressed under the D2 receptor (Drd2) promoter. We show that while the wild-type MSN tonic current pattern demonstrates a high degree of variability, tonic current patterns from β3f/fDrd2 mice are narrow, suggesting that the β3 subunit is essential to striatal MSN GABA-mediated tonic current. Our data also suggest that a distinct population of synaptic receptors upregulate due to β3 subunit removal. Further, deletion of this subunit significantly decreases the D2+ MSN excitability. These results offer insight for target mechanisms in Parkinson’s disease, where symptoms arise due to the imbalance in striatal D1+ and D2+ MSN excitability and output.